Peralkynylated Tetraazaacene Derivatives. Issue 5 (16th December 2019) - Reiss, Hilmar; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F.
Abstract: The synthesis of a decaethynylated tetraazapentacene is described. It was obtained by a combination of condensation reactions giving the two pyrazine rings and subsequent consecutive Stille‐type couplings. This is the first example of any higher (hetero)acene that is peralkynylated. The presence of the four nitrogen atoms removes the peri interaction of the substituted alkyne groups, giving this rock‐stable and highly twisted heteroacene. Abstract : Rock‐stable and highly twisted heteroacene : The synthesis of a decaethynylated tetraazapentacene is described. It was obtained by a combination of condensation reactions giving the two pyrazine rings and subsequent consecutive Stille‐type couplings. This is the first example of any higher (hetero)acene that is peralkynylated (see scheme).